Strategi Promosi melalui Analisis SWOT pada Glamping (Glamour Camping) Dinsy LSB (Lamaru Sunrise Beach ) di Lamaru - Rustika, Ranti; Ghofur, Abdul; Simatupang, Lisnawaty (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2025)
Glamping (Glamour Camping) at Dinsy LSB (Lamaru Sunrise Beach) in Lamaru offers a camping experience that surpasses standard comfort levels by providing amenities akin to typical lodging, thereby allowing tourists to camp comfortably. However, in Balikpapan, glamping has become a highly popular tourist attraction and accommodation, with many entrepreneurs competing to establish their own glamping sites. This poses a threat if Dinsy glamping fails to implement an effective promotional strategy. This study aims to optimize the promotional strategy using SWOT analysis, employing a qualitative research method that includes observation, interviews, and surveys to obtain primary and secondary data. In the SWOT analysis, IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) are determined, and the results are then incorporated into a SWOT diagram. Subsequently, a SWOT Matrix is developed to produce several strategic alternatives. The final step is to determine the most effective strategy through the quadrants resulting from the IFAS and EFAS analysis. The results of the promotional strategy analysis using SWOT indicate that it falls within quadrant 1, or the SWOT matrix is situated in the SO (Strengths and Opportunities) strategy. The SO strategy for Dinsy glamping involves promotional efforts that have not been fully optimized, necessitating the optimal utilization of existing strengths and the exploitation of opportunities.